ANALISIS EKONOMI USAHATANI HORTIKULTURA SEBAGAI KOMODITI UNGGULAN AGRIBISNIS DI DAERAH KABUPATEN PELALAWAN PROVINSI RIAU - Isyandi, B (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2007)
Agribusiness approach is absolutely required to empower the economic of rural community, and it is expected to reduce income disparity of society. The study showed that there are several prime commodities such as banana, durian, orange, and pare, cucumber, kacang panjang. Those commodities would grow in Pelalawan promisingly. The result were considered from several aspects such as economic efficiency, feasibility of land, market possibilities, and community interests.